Dissecting the genetic and phenotypic basis of salinity tolerance in mungbean: Insights from multi-stage phenotyping, GWAS and genomic prediction - Iqbal, Md Shahin; Taylor, Candy M.; Kotula, Lukasz; Malik, Al Imran; Erskine, William (Springer Science+Business Media, 2025)
Mungbean is an important grain legume widely grown in rice-based farming systems of South and Southeast Asia. Salinity stress severely limits mungbean growth and yield, with cultivars differing widely in susceptibility. This study evaluated phenotypic responses and genetic diversity for salinity tolerance in a mungbean mini-core germplasm collection at early vegetative, late vegetative and reproductive stages, grown in soil-filled pots exposed to control (non-saline) and 75 mM NaCl treatments in a temperature-controlled glasshouse. Salinity stress significantly reduced growth, seed yield and related traits, highlighting distinct phenotypic and genotypic responses across growth stages. Genome-wide association studies and genomic prediction (GP) were performed using two SNP datasets: 5991 DArTseq SNPs and 198,474 Illumina whole-genome resequencing (WGRS) SNPs. A range of 18–22 significant genetic associations were identified in the three growth stages, but none were common across these stages. Both SNP datasets showed distinct genomic regions associated with salinity tolerance traits. GP showed potential to predict salinity tolerance-associated traits. Despite their lower genome-wide density, DArTseq SNPs performed similarly to high-density WGRS SNPs in association analyses and GP accuracy, highlighting their potential as a cost-effective genotyping system for efficient and practical commercial breeding applications. Evaluating the effects of significant SNPs revealed seven functional SNPs linked with seven candidate genes encoding callose synthase, ethylene receptor, dynamin-related protein, cytochrome P450, bHLH-type transcription factor and Kinesin-10-type motor protein. The findings demonstrate need for stage-specific breeding approaches and highlight novel genetic resources (including markers and germplasm) for enhancing salinity tolerance in mungbean.